Comprehensive Agrarian Reform Program (CARP): Time to let go - Raul V. Fabella (University of the Philippines, School of Economics (UPSE), 2014)
This paper revisits the record of CARP over the quarter century of its existence. By 2014, 5.05 million of the 5.37m hectares of the targeted agricultural land shall have been distributed. As a program for land asset equity, it shall have accomplished 99% of its target, whopper of a success for a government program. As a program to advance the economic welfare of farmers, it has accomplished the opposite of its stated goals. Productivity has fallen drastically in coconut and sugar and poverty incidence among agrarian reform beneficiaries in agrarian reform communities stood at 54% in 2011 higher than for farmers in general. CARP and CARPER has created a new class of people: the landed poor. The paper then explores the many design and implementation flaws that has brought this sad result among which are: CARP's illegalization of the market for land assets (Section 27) sending Coasean bargains underground and the 5-hectare land ownership ceiling leading to the demise of the legal rural financial market and the flight of private capital. It is time to shift from land equity to farm efficiency. The paper argues for the return of the market in rural production: let productive farmers legally cultivate 10 or more hectares as the market dictates; let PSE-registered firms legally operate agro-industrial farms without land ceiling. Poverty reduction requires the shift of resources and manpower from informal to formal sectors. CARP has done the opposite. To echo the architect of the great Chinese Economic Miracle, Deng Xiaoping: It is time to stop redistributing poverty!
Keywords: 330; CARP; agrarian reform; agriculture; Coase Theorem; Philippines